Terapi Mandiri Kecemasan Klien dengan Penyakit Jantung - Heni Nurhaeni; Mira Rosmiatin; Agus Susanto; Eska Rianti (Jurnal Health Sains, 2022)
Heart disease is a group of conditions that includes coronary heart disease, arrhythmias, heart failure and valvular disease. Heart disease is a major cause of health problems and death and 6.3% of patients treated from COVID-19 isolation rooms have comorbidities. However, in the COVID-19 situation, the mortality rate increased by 22-23% with hemodamic disorders. Many types of heart disease can be prevented or treated with healthy lifestyle choices, medications and/or surgery. Clients with coronary heart disease (CHD) problems often experience anxiety that will significantly worsen their heart health conditions. Stress is a physiological response to stressors that threaten the internal physiological state or psychological well-being of individuals. Anxiety disorders are associated with the onset and progression of heart disease, and in many cases have been associated with cardiovascular disorders, including the incidence of death. Both physiological (autonomic dysfunction, inflammation, endothelial dysfunction, changes in platelet aggregation) and behavioral health mechanisms can explain the relationship between anxiety disorders and coronary heart disease. The association between anxiety disorders and poor heart health, timely and accurate identification and treatment of these conditions is of utmost importance. Thus, clients with CHD require independent rehabilitation in order to suppress the problem. The alternative treatment is through rehabilitation of coronary heart disease clients which is an important part in the management of coronary heart disease clients, which aims to prevent side effects from treatment, recurrence and maintain and increase productivity and quality of life. In addition, effective treatments are available for anxiety disorders in cardiovascular conditions. Further studies are needed to determine whether interventions to treat anxiety disorders ultimately have an impact on mental and cardiovascular health. The aim of this study is to apply self-reliance therapy for Clients with Heart disease in the Community Through Educational Media Independent Therapy of Coronary Heart Disease Client Anxiety (MD-TEMANKU). The results were found with a P Value of 0.0001 on reducing anxiety in CHD Clients in the Community. Therefore, TEMANKU educational media can be one of the inter alternative independent intervention for the client's condition of heart disea